Rearing of Octopus vulgaris paralarvae: Present status, bottlenecks and trends - Iglesias, J.; Sánchez, F.J.; Bersano, J.G.F.; Carrasco, J.F.; Dhont, J.; Fuentes, L.; Linares, F.; Muñoz, J.L.; Okumura, S.; Roo, J.; van der Meeren, T.; Vidal, E.A.G.; et al. (Aquaculture, 2007)
Due to the high mortality rates and poor growth generally observed in Octopus vulgaris paralarval rearing experiments, it was decided to organize a working group in order to formulate recommendations to tackle this problem. Over a dozen scientists representing the most active current research groups related to this subject attended the meeting in Vigo, Spain, in November 2005. The aim of this working group was to determine the bottlenecks that prevent success in paralarval rearing, define the most appropriate rearing conditions, and identify required future research. This paper describes rearing techniques for the O. vulgaris paralarvae used by the different research participant teams, with regard to tank systems, feeding environment, and diets ( Artemia, crustacean zoeae, sandeel flakes, copepods, etc.). Additionally, it includes other related themes such as the culture of Artemia and copepods, organisms that are commonly used in paralarval rearing. When embarking on O. vulgaris rearing it is advised to use prey rich in DHA (docosaenoic acid, 22:6n-3) and EPA (eicosapentaenoic acid, 20:5n-3), and with high DHA/EPA ratio. Such prey could be enriched Artemia, accompanied or not by crustacean zoeae or any microdiet. It is also recommended that, in future studies, values of growth and survival rates are recorded at the beginning of the benthic phase, in order to compare them to successful previous studies. Dry weight and DHA/EPA ratio of paralarvae may also be good criteria to define paralarval viability and evaluate success of the rearing system. It is further concluded that the nutritional aspect is the most important factor influencing larval mortality. Certain lipids (phospholipids, cholesterol, and polyunsaturated fatty acids), amino acids (lysine, leucine and arginine), and essential elements ( e.g. copper) play a relevant role in the larval nutrition. It is believed that the PUFA content, especially DHA and EPA, constitutes one of the basic nutritional requirements. Regarding new research lines, no standardized system for paralarval rearing exists, and it is essential to make progress on this issue. Research on nutritional requirements is considered an area of highest priority, especially the development of a specific enrichment for Artemia, the search for alternative live preys, and the development of suitable formulated diets.